The impact of parental divorce on children's primary and secondary education attainment levels - Suryadewi, Ni Putu Cyntia (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Divorce is a significant life event that can have profound effects on children, particularly in their educational attainment. Previous research suggests that parental divorce can lead to various negative consequences, including psychological distress, social instability, and economic challenges. However, there is limited empirical evidence examining the impact of parental divorce on children's educational attainment in Indonesia. Methods: This study utilizes data from the Indonesian Family Life Survey (IFLS) waves 3, 4, and 5 to examine the educational outcomes of children with divorced parents compared to those with married parents. The analysis explores the relationship between parental divorce and children's educational attainment while considering potential influencing factors such as maternal characteristics and the possibility of reverse causality. Findings: The study found that children from divorced families generally had lower educational attainment than those from intact families. However, children whose parents were currently divorced had better educational outcomes than children whose parents remained married. This paradoxical finding suggests the influence of factors such as maternal education and potential reverse causality. Additionally, the study found that the age at which divorce occurs plays a crucial role divorce at an early age has a more negative impact on educational attainment due to children's higher dependency on parents and limited coping mechanisms. However, no significant differences were found between boys and girls in terms of educational outcomes after divorce. Conclusions: Parental divorce negatively impacts children's educational attainment, primarily due to economic hardship, changes in parenting roles, and psychological distress. However, some children from currently divorced families show better educational outcomes, possibly due to maternal characteristics and other mediating factors. Novelty/Originality of this Article: This study contributes to the existing literature by providing empirical evidence on the impact of parental divorce on children's educational attainment in Indonesia, a context with limited prior research.